Risk Factors for Premature Rupture of the Membranes: Faktor Resiko Ketuban Pecah Prematur - Turlina, Lilin; Ummah, Faizatul; Sulistyowati (Jurnal Kebidanan Midwiferia, 2020)
The incidence of premature rupture of membranes (PRM) ranges from 8-10% at term pregnancy and 1% in preterm pregnancy. The incidence of PRM at RSUD dr. SoegiriLamongan in 2017 amounted to 16,43%. The purpose of this study was to analyze risk factors of the occurrence of premature rupture membranes in RSUD Dr. SoegiriLamongan. The research used descriptive analytical method with cross sectional approach. The sample is 268 maternity mothers, divided into 134 mothers giving birth with PRM and 134 normal maternity mothers at Dr. Soegiri Lamongan on 2018. Sampling is done by simple random sampling. Data collection uses patient medical record and with multivariate multiple logistic regression analysis.The results showed that presentation abnormalities with a p value of 0.045 <0.05 and CPD with a p value of 0.002 <0.05. Based on the Odds Ratio (OR) values ​​as follows: Maternal age OR 1,141, OR parity 0.933, OR fetal presentation 2,779, OR Twins 1,394, OR CPD 6. and OR Large infants 0.783.Meaning that there was a significant influence between fetal presentation and CPD on PRM.